Pertanggungjawaban Pidana Terhadap Anak Pelaku Tindak Pidana Kekerasan (Studi Putusan Nomor 21/Pid.Sus-Anak/2023/PN Pdg) - Prianto, Iga Suci Ervinda; Prawitasari, Nining Yurista (Universitas Pahlawan Tuanku Tambusai, 2024)
Children as human resources are the next generation and leaders in the future. However, the times and lack of supervision of children often lead to situations where children become victims or perpetrators of criminal acts, including violent crimes. This study aims to find out how criminal responsibility for children perpetrators of violent crimes and how the Judge's Consideration in deciding the case of Children as Perpetrators of Violent Crimes. This research method used is normative juridical law research with a statutory approach and a case approach in Decision Study Number 21/Pid.Sus-Anak/2023/PN Pdg, Based on the results of the study shows that how the criminal responsibility of children as perpetrators of violent crimes and the judge's consideration in imposing criminal sentences on children perpetrators of violent crimes based on juridical considerations and non-juridical.